Pre- and post-season heart rate variability in adolescent cross-country skiers - Hedelin, R.; Wiklund, U.; Bjerle, P.; Henriksson-Larsen, K. (Scandinavian Journal of Medicine & Science in Sports, 2000)
To investigate the effects on cardiac autonomic control after a competitive cross-country skiing season, 9 females and 8 males, 16-19 years old, performed tilt-table heart rate variability (HRV) recordings and incremental treadmill tests before (August), and after (April the following year) the most intensive period of training and competition. Spectral analysis of HRV showed increased total variability at rest and reduced low frequency variability in the tilted position (LFtilt) at the second test (P<0.05). The female subgroup showed consistently higher high frequency (HF) and total heart rate variability than males. Total run time (RunT) increased from 18.5+/-1.9 min to 19.4+/-1.7 min (mean+/-SD) in the entire group (P<0.05), while VO2max only showed a non-significant increase (0.05<P<0.10). Submaximal heart rates (HRsubm) were reduced by an average of 4 beats (P<0.01) but maximal HR was unchanged. Performance data suggest a positive training effect. Following training, the increased total HRV the reduced LFtilt (both at rest), and the lower submaximal heart rates indicate an altered control of heart rate both at rest and during exercise. The consistently higher HF and total variability in the females indicate an increased parasympathetic activity in females compared with males.